PENGARUH MODEL PEMBELAJARAN BUZZ GROUP BERBASIS CATUR PRAMANA TERHADAP PEMAHAMAN KONSEP IPAS KELAS IV SEKOLAH DASAR GUGUS II KECAMATAN BUSUNGBIU - Ni Kadek Mirah Dwipayanti; Ni Nyoman Kurnia Wati; I Made Ari Winangun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was driven by the low understanding of science (IPAS) concepts among fourth-grade elementary school students due to the dominance of conventional learning models. The study aimed to analyze the effect of the Buzz Group learning model based on Catur Pramana on the understanding of science concepts. This research was a quasi-experimental study using a Non-equivalent Control Group Design. The population of this study consisted of fourth-grade students in Cluster II, Busungbiu District. The sample was selected using a random sampling technique, resulting in 28 students in the experimental group and 21 students in the control group. Data on students' understanding of science concepts were collected through an essay test consisting of 20 validated items. The data were analyzed using descriptive statistics and inferential statistics (Independent Sample T-test). The results showed that the t-count (14.201) was greater than the t-table (2.013) at a significance level of 0.05. Furthermore, the average N-gain score for the experimental group was 0.72 (High category), while the control group was 0.31 (Medium category). It can be concluded that the Buzz Group learning model based on Catur Pramana has a significant effect on the understanding of science concepts among fourth-grade students. This model provides an innovative alternative for teachers to enhance student participation and conceptual mastery through systematic stages of observation and logical reasoning.